Nepal : Request for an Arrangement Under the Extended Credit Facility -Press Release; Staff Report; Debt Sustainability Analysis; Staff Supplement; Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report ;, 2022)
The COVID-19 pandemic severely impacted Nepal's economy. Tourist arrivals collapsed, domestic activity plummeted, and remittances have been volatile. As a result, balance of payments and fiscal financing gaps emerged. After growth was lower than expected in 2019/20, a gradual resumption in economic activity and a corresponding surge in imports and related tax receipts led to higher growth and improved fiscal outturns in 2020/21. However, important fiscal and external financing needs remain to support the COVID-19 response, facilitate a continued recovery, and maintain a comfortable level of reserves.